FRI0497 What choices do rheumatologist make in escalating dmard therapy in early psa?. (15th June 2017) - Luime, J; Tchetverikov, I; Wervers, K; Gerards, A; Kok, M; Appels, C; Groenendael, H van; Graaff, W vd; Korswagen, L-A; Veris, J; Hazes, M; Vis, M; et al.
Abstract : Background: Psoriatic arthritis (PsA) is a multifaceted disease. Objectives: We aimed to evaluate change in medication over time guided by joints, skin, enthesis, low back pain and dactylitis in newly diagnosed PsA patients Methods: Newly diagnosed PsA patients were included in the Dutch Early south-west Psoriatic Arthritis cohoRt (DEPAR) study between August 2013 and March 2016. Initial drug treatment and escalation of therapy were described for all patients. Drivers of treatment changes in the first year were evaluated by mixed ordered ordinal regression with outcome treatment change and variables joints (66/68 count), skin (PASI), entheses (LEI and MASES), dactylitis (LDI) and axial disease (BASDAI) Results: 323 patients had had baseline assessment in March 2016. Their average age was 50.0 years (SD 13.8) and 49% were male. 80% patients had arthritis (19% monoarthritis, 39% oligoarthritis and 23%polyarthritis), 9% had an enthesitis subtype, 2% axial disease and 9% dactylitis. Initial treatment consisted of methotrexate (MTX) (52%), in 7% of other synthetic disease modifying antirheumatic drugs (sDMARDs) and due to treatment of psoriasis 3% biologicals. Within the different phenotypes MTX was most frequently started in polyarthritis (84%) followed by oligoarthritis (63%), monoarthritis (33%) and other phenotypes (5%). At 12 months 70% (n=148) stayed on the initial drug. Of those switched, 9 started MTX, within the initial MTX users (n=74) almost equal percentages stopped, switched to metoject or biological (4%). A smaller percentage (2%) switch to leflunomide. Changes in medication were driven by swollen joint count and the presence of dactylitis (Table 1 ) Conclusions: MTX was initiated in about half of the early PsA patients. The majority of patients were kept on the initial treatment strategy in first year. Failure on initial drug led to variation in subsequent drugs with additional start of other sdmards, switch subcutaneuous MTX, to other sdmards or to biological dmards. Treatment change was driven by Swollen Joint Count and presence of Dactylitis. Skin, Enthesis and Axial disease did not play a role in escalating treatment. Disclosure of Interest: None declared